Coordinated observations of the red dwarf flare star EV Lac in 1998 - Alekseev, I.Yu.; Antov, A.P.; Avgoloupis, S.J.; Beskin, G.M.; Borisov, N.V.; Chalenko, V.E.; Contadakis, M.E.; Gershberg, R.E.; Khalak, V.R.; Konstantinova-Antova, R.K.; Larionov, V.M.; Panferova, I.P.; et al. (Кинематика и физика небесных тел, 2001)
The results of photometric studies of the flare star EV Lac obtained in the course of cooperative observations in 1998 are presented. No significant brightness variations in IR were found from simultaneous observations of the star in UBVRI and H bands, in coincidence with the observed optical flares. Within the framework of the zonal spottedness model of stars the EV Lac surface inhomogeneity parameters are estimated.